Intestine-derived fibroblast growth factor 19 alleviates lipopolysaccharide-induced liver injury by regulating bile acid homeostasis and directly improving oxidative stress - Xiaomeng Tang; Jingjing Ning; Yilin Zhao; Shuyun Feng; Lujing Shao; Tiantian Liu; Huijie Miao; Yucai Zhang; Chunxia Wang (Journal of Intensive Medicine)
Background: Cholestasis plays a critical role in sepsis-associated liver injury (SALI). Intestine-derived fibroblast growth factor 19 (FGF19) is a key regulator for bile acid homeostasis. However, the roles and underlying mechanisms of FGF19 in SALI are still unclear. Methods: We conducted a case–control study that included 58 pediatric patients aged from 1 month to 14-years-old diagnosed with sepsis at Shanghai Children's Hospital from January to December 2018 and 30 healthy individuals. The serum FGF19 levels of these patients with sepsis were analyzed and compared with those of healthy controls. Recombinant human FGF19 was intravenously injected in mice once a day for 7 days at a dose of 0.1 mg/kg body weight before lipopolysaccharide (LPS) treatment. Liver bile acid profiles and the gene expression involved in bile acid homeostasis were investigated in the mice groups. Metabolomic data were further integrated and analyzed using Ingenuity Pathways Analysis (IPA) software. In the in vitro analysis using HepG2 cells, the influence of FGF19 pretreatment on reactive oxygen species (ROS) production and mitochondrial dysfunction was analyzed. Compound C (CC), an inhibitor of AMP-activated protein kinase (AMPK) activation, was used to confirm the roles of AMPK activation in FGF19-mediated hepatoprotective effects. Results: Serum FGF19 levels were significantly lower in children with sepsis than in healthy controls (115 pg/mL vs. 79 pg/mL, P=0.03). Pre-administration of recombinant human FGF19 alleviated LPS-induced acute liver injury (ALI) and improved LPS-induced cholestasis in mice. Moreover, FGF19 directly reversed LPS-induced intracellular ROS generation and LPS-decreased mitochondrial membrane potential in vitro and in vivo, resulting in hepatoprotection against LPS-induced apoptosis. More importantly, the inhibition of AMPK activity partially blocked the protective effects of FGF19 against LPS-induced oxidative stress and mitochondrial dysfunction. Conclusions: Intestine-derived FGF19 alleviates LPS-induced ALI via improving bile acid homeostasis and directly suppressing ROS production via activating the AMPK signaling pathway.